Effect of linkage on sibship determination based on likelihood ratio. (December 2015) - Morimoto, Chie; Manabe, Sho; Kawai, Chihiro; Fujimoto, Shuntaro; Tamaki, Keiji
Abstract: In forensic genetics, increasing the number of short tandem repeat (STR) loci is an efficient strategy to achieve a high likelihood ratio (LR) for sibship determination. However, as the number of loci increases, the effect of linkage among the loci may become more pronounced. Hence, we evaluated the effect of linkage on sibship determination when analyzing multiple loci including linked loci. We investigated LR value variation in two linked loci by changing the recombination rate and allele frequencies. We then compared LR values with values calculated without considering linkage, using computationally generated genotypes of sibling pairs. These results suggested that the effect of linkage on LR values in sibship determination is affected by the identity by state of the loci, allele frequencies, and number of loci. Therefore, linkage must be considered to calculate rigorous LR values.